CASE STUDY OF THE RADIOGRAPHER CREDENTIAL PROGRAM AS A STANDARD FOR SLEMAN REGIONAL HOSPITAL, 2019 - Dani Yusuf (Jurnal Admmirasi, 2021)
Background : In order to maintain clinical governance in the radiology installation, it is necessary to do the radiographer’s credential program as it serves to collect, Verify and evaluate educational licenses, training, competence, And experience of existing health workers. Credentials are an evaluation process by the hospital of a health worker to determine whether the person concerned is worthy of a clinical assignment and clinical authority to carry out certain medical care/actions within the hospital environment for a certain period.Purpose : To analyze the perceptions of radiographers and relevant policy makers, about the process of implementing the credential program for the radiographer profession, especially in RSUD Sleman.Methods : Methods of data collection through in-depth interviews with radiographers and policy makers, And documentary studies related to the radiographer’s credential program in hospitals. For the result of the research, the radiographer’s credential were analyzed using qualitative methods. The location is in Sleman hospital, Yogyakarta.Results : From the analysis of the radiographer’s perception of the credential program, it was found that the implementation of the radiographer’s credentials at the Sleman Hospital was in accordance with the existing mechanism.Conclusion : From the research result, it can be concluded that the implementation of credentials at the Sleman Hospital has been carried out independently, but the implementation of the radiographer’s credentials program independently needs to be evaluated regarding the implementation mechanism. Because the credential program is only limited to the administrative aspect (portfolio), This is still less than ideal and objective, Considering the increasingly complex services available in radiology installations. More competency assessment methods are needed to maintain accountability and competence of health workers in order to ensure that patients get safe and quality health services.